Cellulose nanofibres (CNF) for sulphate resistance in cement based systems. (May 2019) - Goncalves, Jose; El-Bakkari, Mounir; Boluk, Yaman; Bindiganavile, Vivek
Abstract: Cellulose nanofibres (CNF) are employed for the first time to address sulphate penetration and subsequent dimensional change in the cementitious system. Using four different Portland cement based binders, paste and mortar mixtures were prepared to have up to 0.5% dry CNF by volume fraction. After 28 days of moist curing, the specimens were subjected to accelerated sulphate attack for 12 weeks. Unidirectional penetration of sulphate was determined according to a modified ASTM C114 method. Alongside, the change in length was measured as per ASTM C 1012. The results show that CNF visibly reduces the penetration of sulphate ions inside the cementitious system. As well, it effects a marked reduction in the Ettringite produced and the associated expansion. Of particular significance to the construction industry is that at 0.3–0.5%, CNF imparts as much resistance to Type GU Portland cement against sulphate attack, as the specially formulated sulphate resistant cements.